Homicide and Organized Crime in England. (August 2013) - Hopkins, Matt; Tilley, Nick; Gibson, Kate
This article reports results of a study identifying and analyzing the 17 homicides (from a total 696 recorded non-terrorist homicides) committed as part of organized crime in England and Wales in 2005-2006. Homicides related to organized crime were found to follow from inter group rivalries, tensions within the same organized crime group, or police/citizen resistance during armed robbery. The motivations of the homicides can be broadly categorized as instrumental or expressive. Suggestions are made for further research on the conditions surrounding such homicides and on the relative rarity of organized crime related homicides in Britain.